Case Report: Infant With Congenital Adrenal Hyperplasia and 47,XXY - Song, Sophia Q.; Gropman, Andrea; Benjamin, Robert W.; Mitchell, Francie; Brooks, Michaela R.; Hamzik, Mary P.; Sampson, Kira; Kommareddi, Ritika; Sadeghin, Teresa; Samango-Sprouse, Carole A. (Frontiers in Genetics, 2022)
Congenital adrenal hyperplasia is a group of autosomal recessive disorders in which enzymes in the cortisol biosynthesis pathways are disrupted by gene mutations. The most common form of congenital adrenal hyperplasia, caused by 21-hydroxylase deficiency, is characterized by decreased cortisol and aldosterone synthesis and excessive androgen production. Adult height is often compromised in affected patients. Intellectual capability remains intact in patients with congenital adrenal hyperplasia caused by 21-hydroxylase deficiency, based on previous studies. 47,XXY (KS) is a sex chromosomal aneuploidy that manifests with hypergonadotropic hypogonadism, tall stature, and variable intellectual and behavioral dysfunction. This clinical report describes an infant with 21-hydroxylase deficiency congenital adrenal hyperplasia and 47,XXY. The results of his neurodevelopmental, endocrine, neurological, and physical therapy evaluations during his first 22 months are included and were normal. This is the first published case investigating the neurodevelopmental profile of a patient with the combination of these two genetic disorders.